Marvin - A Conversational Agent Based Interface for the Study of Information Sciences - Mikelić Preradović, Nives (Array, 2009)
In this paper we present initial results of the ongoing project, building a Conversational Agent (chatterbot) - Marvin. Marvin is designed to simulate intelligent conversation with students of Information Sciences at the Faculty of Humanities and Social Sciences in Zagreb. It is capable of providing basic feedback to students via textual methods. The primary goal of this work is to inform the user of points of interest, to provide support, capture data from the user and promote study of information sciences. Furthermore, the goal is to enhance the presentation of information to students, especially information regarding the undergraduate study, obligatory and elective courses, ECTS (European Credit Transfer System) points and exams. Finally, the objective is to teach the students how to improve the quality of user experience using human-like conversational agents.